2019
DOI: 10.1155/2019/8586167
|View full text |Cite
|
Sign up to set email alerts
|

TG : HDL-C Ratio Is a Good Marker to Identify Children Affected by Obesity with Increased Cardiometabolic Risk and Insulin Resistance

Abstract: Metabolic syndrome (MetS) is an important predictor of cardiovascular diseases in adulthood. This study aims to examine the clinical utility of triglyceride to high-density lipoprotein ratio (TG : HDL-C) in identifying cardiometabolic risk and insulin resistance (IR) among children with obesity, in comparison with MetS as defined by the International Diabetes Federation (IDF). Data of 232 children with obesity aged 10–16 years were obtained from our study, MyBFF@school study, conducted between January and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 46 publications
3
27
1
Order By: Relevance
“…Even though previous studies have revealed that TG/HDL-C ratio as a good surrogate marker to predict IR in obese children or youth [34,35], in this study, we found it is not a significant predictor of IR in patients with newly diagnosed T2DM. However, we found that, the ratio of TG/HDL-C was increased (p = 0.28) across the insulin quartile suggesting its positive association with IR.…”
Section: Plos Onecontrasting
confidence: 95%
“…Even though previous studies have revealed that TG/HDL-C ratio as a good surrogate marker to predict IR in obese children or youth [34,35], in this study, we found it is not a significant predictor of IR in patients with newly diagnosed T2DM. However, we found that, the ratio of TG/HDL-C was increased (p = 0.28) across the insulin quartile suggesting its positive association with IR.…”
Section: Plos Onecontrasting
confidence: 95%
“…In previous studies, TG/HDL was often used to evaluate insulin resistance [34][35][36][37][38]. Recent studies have found a correlation between TG/HDL and the incidence of diabetes [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…HOMA-IR was calculated using the following formula: INS (mIU/L) ×FPG (mmol/L)/22.5. A HOMA-IR value >4 is considered IR, and values ≤4 deemed insulin sensitive (IS) ( 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%